let D, D9, E be non empty set ; :: thesis: for d being Element of D
for d9 being Element of D9
for i being natural Number
for F being Function of [:D,D9:],E
for T being Tuple of i,D
for T9 being Tuple of i,D9 holds F .: ((T ^ <*d*>),(T9 ^ <*d9*>)) = (F .: (T,T9)) ^ <*(F . (d,d9))*>

let d be Element of D; :: thesis: for d9 being Element of D9
for i being natural Number
for F being Function of [:D,D9:],E
for T being Tuple of i,D
for T9 being Tuple of i,D9 holds F .: ((T ^ <*d*>),(T9 ^ <*d9*>)) = (F .: (T,T9)) ^ <*(F . (d,d9))*>

let d9 be Element of D9; :: thesis: for i being natural Number
for F being Function of [:D,D9:],E
for T being Tuple of i,D
for T9 being Tuple of i,D9 holds F .: ((T ^ <*d*>),(T9 ^ <*d9*>)) = (F .: (T,T9)) ^ <*(F . (d,d9))*>

let i be natural Number ; :: thesis: for F being Function of [:D,D9:],E
for T being Tuple of i,D
for T9 being Tuple of i,D9 holds F .: ((T ^ <*d*>),(T9 ^ <*d9*>)) = (F .: (T,T9)) ^ <*(F . (d,d9))*>

let F be Function of [:D,D9:],E; :: thesis: for T being Tuple of i,D
for T9 being Tuple of i,D9 holds F .: ((T ^ <*d*>),(T9 ^ <*d9*>)) = (F .: (T,T9)) ^ <*(F . (d,d9))*>

let T be Tuple of i,D; :: thesis: for T9 being Tuple of i,D9 holds F .: ((T ^ <*d*>),(T9 ^ <*d9*>)) = (F .: (T,T9)) ^ <*(F . (d,d9))*>
let T9 be Tuple of i,D9; :: thesis: F .: ((T ^ <*d*>),(T9 ^ <*d9*>)) = (F .: (T,T9)) ^ <*(F . (d,d9))*>
set p = T ^ <*d*>;
set q = T9 ^ <*d9*>;
set pq = F .: (T,T9);
set r = F .: ((T ^ <*d*>),(T9 ^ <*d9*>));
set s = (F .: (T,T9)) ^ <*(F . (d,d9))*>;
A1: len T9 = i by CARD_1:def 7;
then A2: len (T9 ^ <*d9*>) = i + 1 by FINSEQ_2:16;
A3: len T = i by CARD_1:def 7;
then A4: len (F .: (T,T9)) = i by ;
len (T ^ <*d*>) = i + 1 by ;
then A5: len (F .: ((T ^ <*d*>),(T9 ^ <*d9*>))) = i + 1 by ;
then A6: dom (F .: ((T ^ <*d*>),(T9 ^ <*d9*>))) = Seg (i + 1) by FINSEQ_1:def 3;
A7: now :: thesis: for j being Nat st j in dom (F .: ((T ^ <*d*>),(T9 ^ <*d9*>))) holds
(F .: ((T ^ <*d*>),(T9 ^ <*d9*>))) . j = ((F .: (T,T9)) ^ <*(F . (d,d9))*>) . j
let j be Nat; :: thesis: ( j in dom (F .: ((T ^ <*d*>),(T9 ^ <*d9*>))) implies (F .: ((T ^ <*d*>),(T9 ^ <*d9*>))) . j = ((F .: (T,T9)) ^ <*(F . (d,d9))*>) . j )
assume A8: j in dom (F .: ((T ^ <*d*>),(T9 ^ <*d9*>))) ; :: thesis: (F .: ((T ^ <*d*>),(T9 ^ <*d9*>))) . j = ((F .: (T,T9)) ^ <*(F . (d,d9))*>) . j
now :: thesis: F . (((T ^ <*d*>) . j),((T9 ^ <*d9*>) . j)) = ((F .: (T,T9)) ^ <*(F . (d,d9))*>) . j
per cases ( j in Seg i or j = i + 1 ) by ;
suppose A9: j in Seg i ; :: thesis: F . (((T ^ <*d*>) . j),((T9 ^ <*d9*>) . j)) = ((F .: (T,T9)) ^ <*(F . (d,d9))*>) . j
Seg (len T) = dom T by FINSEQ_1:def 3;
then A10: (T ^ <*d*>) . j = T . j by ;
A11: Seg (len (F .: (T,T9))) = dom (F .: (T,T9)) by FINSEQ_1:def 3;
Seg (len T9) = dom T9 by FINSEQ_1:def 3;
then A12: (T9 ^ <*d9*>) . j = T9 . j by ;
j in dom (F .: (T,T9)) by ;
hence F . (((T ^ <*d*>) . j),((T9 ^ <*d9*>) . j)) = (F .: (T,T9)) . j by
.= ((F .: (T,T9)) ^ <*(F . (d,d9))*>) . j by ;
:: thesis: verum
end;
suppose A13: j = i + 1 ; :: thesis: F . (((T ^ <*d*>) . j),((T9 ^ <*d9*>) . j)) = ((F .: (T,T9)) ^ <*(F . (d,d9))*>) . j
then ( (T ^ <*d*>) . j = d & (T9 ^ <*d9*>) . j = d9 ) by ;
hence F . (((T ^ <*d*>) . j),((T9 ^ <*d9*>) . j)) = ((F .: (T,T9)) ^ <*(F . (d,d9))*>) . j by ; :: thesis: verum
end;
end;
end;
hence (F .: ((T ^ <*d*>),(T9 ^ <*d9*>))) . j = ((F .: (T,T9)) ^ <*(F . (d,d9))*>) . j by ; :: thesis: verum
end;
len ((F .: (T,T9)) ^ <*(F . (d,d9))*>) = (len (F .: (T,T9))) + 1 by FINSEQ_2:16;
hence F .: ((T ^ <*d*>),(T9 ^ <*d9*>)) = (F .: (T,T9)) ^ <*(F . (d,d9))*> by ; :: thesis: verum